2021
DOI: 10.1002/ange.202106117
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Directed Modification of Active Matrix Metalloproteases: Activity‐based Probes with no Photolabile Group

Abstract: Activity‐based probes enable discrimination between the active enzyme and its inactive or inactivated counterparts. Since metalloproteases catalysis is non‐covalent, activity‐based probes targeting them have been systematically developed by decorating reversible inhibitors with photo‐crosslinkers. By exploiting two types of ligand‐guided chemistry, we identified novel activity‐based probes capable of covalently modifying the active site of matrix metalloproteases (MMPs) without any external trigger. The abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…This approach notably enabled monitoring of the activity of MT1-MMP in cells and in vivo but required genetic manipulations incompatible with native conditions. More recently, and inspired by the ligand-directed chemistry developed by the group of Itaru Hamachi (Tamura and Hamachi, 2019), a new type of MMP-directed ABPs has been published (Kaminska et al, 2021). The affinity probe harbors a phosphinic pseudopeptide scaffold and an N-acyl-Nalkyl sulfonamide cleavable electrophile in P 3 ' (Fig.…”
Section: Activity-based Probes To Crosslink Active Mmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach notably enabled monitoring of the activity of MT1-MMP in cells and in vivo but required genetic manipulations incompatible with native conditions. More recently, and inspired by the ligand-directed chemistry developed by the group of Itaru Hamachi (Tamura and Hamachi, 2019), a new type of MMP-directed ABPs has been published (Kaminska et al, 2021). The affinity probe harbors a phosphinic pseudopeptide scaffold and an N-acyl-Nalkyl sulfonamide cleavable electrophile in P 3 ' (Fig.…”
Section: Activity-based Probes To Crosslink Active Mmpsmentioning
confidence: 99%
“…Through the development of the first chemical probes able to covalently modify active MMPs with no photoactivation (Kaminska et al, 2021), a major step has been taken, and the proteomic profiling of active MMPs in vivo should become amenable. However, to limit the background labeling and to expand this approach to a larger set of MMPs, several adjustments in the structure of activity-based probes will probably be necessary.…”
Section: F the Future Of Mmp-directed Molecular Probesmentioning
confidence: 99%
“…These studies found that increased invasiveness and metastatic propensity were associated with increases in uPA and tPA activity. For labeling metalloproteases, covalent probes have been developed using photoreactive or spontaneously reactive variants of noncovalent inhibitors ( 391 , 394 , 395 ). However, these approaches have not yet been widely adopted, partly due to challenges in achieving uniform labeling efficiencies across different enzymes.…”
Section: Identifying the Villains And Their Modus Operandi—an Evolvin...mentioning
confidence: 99%
“…However, these approaches have not yet been widely adopted, partly due to challenges in achieving uniform labeling efficiencies across different enzymes. This limitation arises because the proximity labeling depends upon the presence of a well-placed nucleophile on the enzyme ( 395 , 396 ).…”
Section: Identifying the Villains And Their Modus Operandi—an Evolvin...mentioning
confidence: 99%
“…[4][5][6][7][8][9] ZBGs including hydroxamic acids, phosphinic acids, phosphonamides and sulfonamides have been incorporated into AfBPs to target metalloproteins including matrix metalloproteases (MMPs) and carbonic anhydrases (CA). [10][11][12][13][14][15] However, this existing library of AfBPs employ a tiny fraction of all known ZBGs. 16,17 Furthermore, only a small subset of these AfBPs have been successfully translated to profiling studies in live cells.…”
Section: Introductionmentioning
confidence: 99%